Monolithic tandem solar cells comprising electrodeposited CuInSe2 and perovskite solar cells with a nanoparticulate ZnO buffer layer - Jang, Yoon Hee; Lee, Jang Mi; Seo, Jung Woo; Kim, Inho; Lee, Doh-Kwon (ROYAL SOC CHEMISTRY, 2017)
We demonstrate semi-transparent inverted planar perovskite solar cells (PSCs) for monolithic tandem construction with an electrodeposited CuInSe2 (CISe) solar cell. To eliminate the severe degradation of perovskite/PCBM layers during a transparent conducting oxide sputtering process, a thin ZnO nanoparticle (NP) layer is introduced onto the electron-extracting PCBM layer by a simple solution process without a post-annealing step. It is found that a thin ZnO-NP layer with an optimal thickness facilitates the electron transfer from PCBM to the Ag back contact in opaque devices while also helping to protect the underlying layers from plasma-induced damage in semi-transparent devices. As a result, semi-transparent PSC devices with an inverted architecture having a sputtered Al-doped ZnO top electrode are realized with power conversion efficiencies over 10%. In addition, monolithically integrated, two-terminal tandem devices composed of solution-processed CISe/perovskite are successfully fabricated, demonstrating an efficiency of 11% with a negligible degree of hysteresis.
Keywords: ORGANOMETAL HALIDE PEROVSKITE; PHOTOVOLTAIC PERFORMANCE; EFFICIENT; RECOMBINATION